Effect of NiCo2O4-modified expanded graphite on heat transfer and storage improvement of CaCl2⋅6H2O. (February 2022) - Xin, Yixiu; Nian, Hongen; Li, Jinhong; Zhao, Jiaqing; Tan, Xiaoling; Zhou, Yongquan; Zhu, Fayan; Liu, Hongyan; Li, Xiang
Highlights: The thermal conduction channel of in-situ NiCo2 O4 was constructed in the pores of EG. The hydrophilicity of EG was significantly improved, which was beneficial to the encapsulation of salt hydrate. The CaCl2 ⋅6H2 O-based CPCM achieved both thermal conductivity improvement and reliability enhancement. The innovative CPCM in this study possessed comprehensive and great thermal characteristics. Abstract: The efficient heat energy storage and conversion can be achieved by form-stable composite phase change material (CPCM) to cope with energy supply and demand imbalances in time and space. The modification of expanded graphite (EG) is important in promoting the phase change behavior of inorganic CPCM. The NiCo2 O4 with spinel structure has an excellent thermal conduction channel and great hydrophilia. In this study, the in-situ NiCo2 O4 was adopted to optimize the thermal conductivity and improve the thermal reliability of CaCl2 ⋅6H2 O (CCH)-based CPCM. It was found that the obtained CPCM exhibited the enhanced thermal conductivity (4.652 W⋅ m   −   1 ⋅ K   −   1 ), which was nearly 8.25 times that of CCH (0.564 W⋅ m   −   1 ⋅ K   −   1 ). The thermal reliability increased, which was ascribable to the improvement of hydrophilicity. Moreover, the CCH-based CPCM showed great chemical compatibility, good energy storage density (149.32 J⋅ g   −   1 ), and optimized apparent activation energy (363.62 kJ⋅mol −1 ). This work will provide new insights into enhanced thermal conductivity and reliability for form-stabilized CPCM by establishing three-dimensional bimetallic oxide channels. Graphical abstract: Image, graphical abstract